2018
DOI: 10.5812/iji.83194
|View full text |Cite
|
Sign up to set email alerts
|

First Sequence Analysis of Genes Mediating Extended-Spectrum Beta-Lactamase (ESBL) bla-TEM, SHV- and CTX-M Production in Isolates of Enterobacteriaceae in Southern Benin

Abstract: The production of extended-spectrum beta-lactamase (ESBL) by Enterobacteriaceae is a global public health problem. The present study was carried out on 156 strains of enteric bacteria isolated from urinary and cervicovaginal fluid samples. Identification of the strains was performed using MALDI-TOF MS and antibiotic susceptibility tests by disk diffusion method on Mueller Hinton agar in accordance with the recommendations of the Antibiogram Committee of the French Society for Microbiology. ESBL genes were soug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…pneumoniae and E. coli are the members of the Enterobacteriaceae family that cause nosocomial infections. Recently, in many parts of the world, antibiotic resistance due to the presence of beta-lactamase enzymes increased against a wide variety of antibiotics (20)(21)(22). In this study, the results indicate a high rate of antibiotic resistance, which is consistent with the results of many studies around the world, but in some studies, this rate of resistance is low, which indicates differences in the pattern of antibiotic use in different regions (23,24).…”
Section: Discussionsupporting
confidence: 89%
“…pneumoniae and E. coli are the members of the Enterobacteriaceae family that cause nosocomial infections. Recently, in many parts of the world, antibiotic resistance due to the presence of beta-lactamase enzymes increased against a wide variety of antibiotics (20)(21)(22). In this study, the results indicate a high rate of antibiotic resistance, which is consistent with the results of many studies around the world, but in some studies, this rate of resistance is low, which indicates differences in the pattern of antibiotic use in different regions (23,24).…”
Section: Discussionsupporting
confidence: 89%
“…The same finding was made by Maina et al, who found in Nairobi, Kenya, that the presence of the SHV gene could predict resistance to Ceftazidime [26]. The coexistence of different resistance genes in gram-negative bacteria may explain their MDR [27] [28]. Therefore, the hospital environment (air, soil, surfaces, equipment) contaminated by MDR bacteria can serve as a reservoir for crosstransmission of these bacteria [29].…”
Section: Discussionsupporting
confidence: 59%
“…Since only a few molecular typing studies have examined E. coli related infections in hospitals in low- and middle-income countries (LMICs), such as Benin, limited information is available on the subtypes that cause infections and their transmission dynamics in LMICs. Genotypic antimicrobial resistance evaluation has been performed mainly by polymerase chain reaction (PCR), which often fails to capture the full complexity of antimicrobial genetic structures ( Anago et al, 2015 ; Koudokpon et al, 2018 ). In recent years, whole-genome sequencing (WGS) has increasingly been used to examine drug-resistant commensal and pathogenic E. coli , providing more complete insight into the genetic structures associated with the evolution of multidrug resistance (MDR) and transmission dynamics ( Punina et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%